Synchrotron far-infrared spectroscopy of corroded steel surfaces using a variable angle of incidence - Lepkova, Katerina; Van Bronswijk, Wilhelm; Pandarinathan, Priya; Gubner, Rolf (Blackwell Publishing, 2014)
Far-infrared spectroscopy, using a synchrotron source, has been used to study carbon steel corroded in CO2-saturated brine in the presence and absence of the corrosion inhibitor 2-mercaptopyrimidine (MPY), which allowed the steel surface roughness to be modified. The effect of the angle of incidence (i, 30–80) on the band intensity and observed bands of the spectra from these surfaces has been determined. For the MPY-treated steel (low surface roughness) the highest band intensity is observed at high i (80) and different bands were observed at different i. In contrast, for the MPY-free steel (high surface roughness) the highest band intensity is observed at low i (30) and spectral content changes were not observed. The results are explained in terms of the roughness of the MPY-treated and MPY-free steels, and their effect on the level of diffusely reflected light of the incident infrared beam.